1992
DOI: 10.1007/bf00684853
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic resistance to anticancer agents in the murine pancreatic adenocarcinoma PANC02

Abstract: PANC02 is a ductal adenocarcinoma of the pancreas that is resistant to every known class of clinically active antitumor agent. To study the mechanism(s) underlying the intrinsic drug resistance of this tumor, a mammary adenocarcinoma (CA-755) that also grows in C57/BL mice and is known to be drug sensitive was used for comparison. PANC02 resistance and CA-755 sensitivity to several antitumor agents and to X-ray therapy was confirmed in mice, and PANC02 also demonstrated relative resistance in tissue culture. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…While several agents have shown a significant inhibition to gether, none of them could induce the regres sion of the tumor when used singly [28]. Our data confirm the suggestion that human pan creatic adenocarcinoma is resistant to most of the effective chemotherapy agents [26,27], Hyperthermia seems to be one of the most im portant agents to enhance the antineoplastic capacity of chemotherapeutic drugs. The pos sibility of enhancing the effect of cytotoxic drugs on tumor cells by means of hyperther mia has been clearly shown by many in vitro and in vivo experiments [29,30].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While several agents have shown a significant inhibition to gether, none of them could induce the regres sion of the tumor when used singly [28]. Our data confirm the suggestion that human pan creatic adenocarcinoma is resistant to most of the effective chemotherapy agents [26,27], Hyperthermia seems to be one of the most im portant agents to enhance the antineoplastic capacity of chemotherapeutic drugs. The pos sibility of enhancing the effect of cytotoxic drugs on tumor cells by means of hyperther mia has been clearly shown by many in vitro and in vivo experiments [29,30].…”
Section: Discussionsupporting
confidence: 78%
“…It is well-known that pancreatic cancer is one of the neoplasms with resistance to every known class of clinically active antitumor agent [26,27], In vitro studies showed 5-FU to have a sufficient antitumor effect in human pancreatic adenocarcinoma cell lines, even at clinically attainable concentrations and expo sure times [13]. With in vivo studies, none of the fluoropyrimidines inhibited human pan creatic cancer cell growth [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic adenocarcinomas are highly angiogenic and fibrotic tumors, and TGFb overexpression in pancreatic cancer correlates with decreased survival (43,44). The Panc02 murine pancreatic adenocarcinoma cell line is highly resistant to chemotherapy and radiotherapy when injected into syngeneic mice (32). While in vitro Panc02 cells are similarly radiosensitive as CT26 cells, in vivo CT26 tumors are markedly more radiosensitive (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Here, we used an immunocompetent C57BL/6 murine model to evaluate antitumor immunity against the pancreatic cancer cell line, PANC02. PANC02 is a chemically induced ductal pancreatic cancer cell line and is resistant to various antitumor agents [20,21]. For that reason, PANC02 cells highly resemble the human counterpart.…”
Section: Discussionmentioning
confidence: 99%